2022
DOI: 10.25105/jkgt.v4i1.14286
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran tingkat kenyamanan pengguna gigi tiruan sebagian lepasan pada lansia penderita xerostomia

Abstract: Background: As someone gets older, changes in saliva and tooth loss are a few of changes that occur in the oral cavity. Dentures are designed to replace missing teeth and can improve mastication, pronunciation, and aesthetics, as well as maintain tissue health and in the oral cavity. Changes in the composition of saliva occur in the elderly, causing saliva production to malfunction and resulting in complaints of dry mouth or xerostomia.reaching the elderly age, the composition of their saliva changes, causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Instructions on maintaining fixed dentures are very important to avoid problems that will arise if not done properly. 15 Objectively, masticatory ability can be assessed by chewing gum and assessing the color change from a score of 1 to 11. 16 The study results from the aspect of masticatory function showed that most respondents were satisfied (86.6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instructions on maintaining fixed dentures are very important to avoid problems that will arise if not done properly. 15 Objectively, masticatory ability can be assessed by chewing gum and assessing the color change from a score of 1 to 11. 16 The study results from the aspect of masticatory function showed that most respondents were satisfied (86.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Routine visits can be made to educate about oral hygiene and motivate patients to maintain oral hygiene. 15 Patients should be informed that a pontic design that provides a space between the pontic surface and the mucosal tissue serves to avoid irritation due to dentures, but patients should maintain additional oral hygiene. Thus, the room does not become a place for plaque accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil kepuasan estetik dari perawatan GTSL pada Tabel 2 ditinjau dari beberapa aspek, yaitu 100% pasien menyatakan puas terhadap susunan gigi dan bentuk gigi sebanyak 100%, lalu diikuti rasa puas pada warna gigi sebanyak 50% dan sangat puas 50%, serta rasa puas sebanyak 100% pada aspek ukuran gigi dan penempatan cengkeram pada perawatan GTSL. Hasil pengukuran kepuasan pasien perawatan GTSL sesuai dengan penelitian sebelumnya yang menunjukkan kepuasan pasien yang tinggi sebanyak 88,4% (Gozali & Teguh, 2022). Perawatan gigi tiruan yang telah dilakukan dapat mendukung dari estetik pasien dengan memperhatikan aspek-aspek susunan, bentuk, warna, ukuran dan letak cengkeram.…”
Section: Evaluasiunclassified